2013
DOI: 10.1063/1.4829556
|View full text |Cite
|
Sign up to set email alerts
|

All-optical signal processing at 10 GHz using a photonic crystal molecule

Abstract: We report on 10 GHz operation of an all-optical gate based on an Indium Phosphide Photonic Crystal Molecule. Wavelength conversion and all-optical mixing of microwave signals are demonstrated using the 2 mW output of a mode locked diode laser. The spectral separation of the optical pump and signal is crucial in suppressing optical cross-talk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…We discuss dynamics, all-optical modulation and frequency conversion at a fast repetition rate (10 GHz). [10]. The interest in the PhC/InP approach has been confirmed by the recent results from DTU, who demonstrated all-optical signal processing [13] and LPN, who introduced hybrid Silicon-InP cavities and demonstrated fast processing [14].…”
Section: Towards Optical Signal Processing Using Nanophotonic Casupporting
confidence: 50%
See 1 more Smart Citation
“…We discuss dynamics, all-optical modulation and frequency conversion at a fast repetition rate (10 GHz). [10]. The interest in the PhC/InP approach has been confirmed by the recent results from DTU, who demonstrated all-optical signal processing [13] and LPN, who introduced hybrid Silicon-InP cavities and demonstrated fast processing [14].…”
Section: Towards Optical Signal Processing Using Nanophotonic Casupporting
confidence: 50%
“…Indium Phosphide photonic crystal cavities have been demonstrated by us and by DTU [10], [11], [12] providing large switching contrast and a fairly fast dynamics, with a typical two time constant relaxation, first observed by NTT in silicon and InGaAsP PhC cavities [9]. In this talk we will focus on the properties of the so-called "photon molecules", resulting form the coupling of two photonic cavities.…”
Section: Towards Optical Signal Processing Using Nanophotonic Camentioning
confidence: 99%
“…In that work it was also found that the nonmonotonous frequency dependence of the Fano transmission spectrum implies an inherent reduction of patterning effects. In contrast, a Lorentzian spectrum, with its monotonously varying tails, faithfully converts (slow) dynamics of the resonance shift into amplitude modulation, limiting the bitrate due to the long carrier lifetime [7][8][9][10][11].Here we experimentally demonstrate that by breaking the symmetry of a Fano structure, the switching properties can be further improved. Furthermore, by employing a nanocavity of the H0-type, which has the smallest mode volume of all known PhC defect cavities [2], we are able to further decrease the switching energy.…”
mentioning
confidence: 73%
“…In that work it was also found that the nonmonotonous frequency dependence of the Fano transmission spectrum implies an inherent reduction of patterning effects. In contrast, a Lorentzian spectrum, with its monotonously varying tails, faithfully converts (slow) dynamics of the resonance shift into amplitude modulation, limiting the bitrate due to the long carrier lifetime [7][8][9][10][11].…”
mentioning
confidence: 91%
“…Other improvements are possible, e.g. the combination with multi-mode 7,34 and multi-port 35 designs to relieve the pump-signal crosstalk limitation as well as employing quaternary InGaAsP material, where carriers are generated through a combination of two-photon and linear absorption 4 , significantly reducing the energy consumption. Considering that the device properties are governed by a quite general coupled mode formalism, we believe that the investigated Fano resonances can be realized using a wide range of structures such as micro-disk or micro-ring resonators 32 .…”
mentioning
confidence: 99%